Insulin Growth Factor-I in Protein-Energy Malnutrition during Rehabilitation in Two Nutritional Rehabilitation Centres in Burkina Faso - S. Kouanda; B. Doulougou; V. De Coninck; L. Habimana; B. Sondo; R. Tonglet; J. M. Ketelslegers; A. Robert (Journal of Tropical Medicine)
Objective. To investigate the relationship between IGF-I and the nutritional status of West-African children hospitalised for nutritional rehabilitation. Patients and methods. A cohort study was performed in two centres for nutritional rehabilitation and education (CREN) in Burkina Faso. Children were followed and the anthropometric data as well as the capillary blood samples were taken on the 7th and on the 14th days after their admission. IGF-I levels were determined from dried blood spots on filter paper on IGF-I RIA, after separation of the IGF-I from its binding proteins, using Sep-Pak chromatography. Results. A total of 59 children was included in the cohort. The IGF-I mean geometric values (SD) were 6.3 (1.4) μg/L on admission, 8.6 (1.8) μg/L at day 7 and 13.6 (2.0) μg/L at day 14. The differences between these values were statistically significant (P<.001). There is a significant correlation between the changes of IGF-I with the change of weight for height Z-score (P = .01). Conclusion. These results suggest that IGF-I can be considered as a potential marker to follow the nutritional status of children admitted in hospital for protein and energy malnutrition.